PENERAPAN MEDIA AUDIO VISUAL SEBAGAI UPAYA MENINGKATKAN MINAT BELAJAR SISWA SD INPRES NDETUWARU - Yuliana Yenita Mete; Jumilah Gago; Melkianus Bernadin Lalong (Jurnal Bionatural, 2025)
The study subjects were 10 fourth-grade students, consisting of 6 boys and 4 girls. Data collection techniques included observation, interviews, documentation, and a questionnaire measuring four indicators of learning interest: enjoyment, interest, attention, and student engagement in learning. The results showed an increase in student interest in learning after the application of audio-visual media. In the pre-cycle, most students were in the "poor" category. After the interventions in the first cycle, interest in learning began to increase to the "moderate" category. In the second cycle, all students showed significant improvement, ranging from "high" to "very high." Audio-visual media has been proven to attract student attention, increase active engagement in the learning process, and create a more enjoyable and meaningful learning environment.